Effect of carbide slag and steel slag as alkali activators on the key properties of carbide slag-steel slag-slag-phosphogypsum composite cementitious materials - Yang, Guihong; Li, Chao; Xie, Wangshan; Yue, Yao; Kong, Chuiyuan; Li, Xiaolong (Frontiers in Materials, 2024)
In order to enhance the utilization of alkaline carbide slag (CS) and steel slag (SS) in solid wastebased cementitious materials (SWBCM). In this study, slag (GGBS) was utilized as the primary material, phosphogypsum (PG) as the sulfat activator, and carbide slag (CS) and steel slag (SS) as the alkali activators to prepare carbide slag-steel slag-slag-phosphogypsum composite cementitious material (CS-SS-GGBS-PG). The impact of partial SS (mass fraction) substitution by CS on the flowability, mechanical properties, softening coefficient, pore solution pH value, hydration heat, and microstructure of CS-SS-GGBS-PG was studied. The hydration products, microstructure, and pore structure of CS-SS-GGBS-PG were studied via XRD, FTIR, TG-DTG, SEM, and MIP. The results show that CS replacement with SS decreases the flowability of CS-SS-GGBS-PG compared to the specimen without CS doping (A0). The addition of CS provides an abundance of Ca 2+ and OH -to facilitate the hydration reaction in the system, prompting CS-SS-GGBS-PG to form more C-(A)-S-H gels and ettringite (AFt) in the early stages. This significantly enhances the 3 and 7 days strength of CS-SS-GGBS-PG. Compared to A0, the sample group with 5% CS substitution for SS showed a respective increase of 400% and 1150% in flexural strength at 3 and 7 days, and an increase of 800% and 1633% in compressive strength. However, if CS is substituted for SS in excess, the system's late hydration process will be inhibited, increasing the volume of harmful pores in the specimen's microstructure and lowering its degree of compactness. This leads to a decrease of 28 days of strength and a deterioration of the water resistance of CS-SS-GGBS-PG. It is advised that the blending ratio of SS to CS be 3:1 in order to maintain equilibrium between the early strength enhancement of CS-SS-GGBS-PG and the stability of strength and water resistance in the latter stage. This study has a positive impact on improving the utilization of CS and SS in SWBCM, reducing the dependence of SWBCM on traditional high-angstrom chemical alkali activators, and promoting the development of SWBCM.